Monitoring of Microbial Safety of Foods Using Lectins: A Review - Vishweswaraiah, Raghu Hirikyathanahalli; Tenguria, Shivendra; Chandrasekhar, B.; Harshitha, C. G.; Gandhi, Kamal; Kumar, Naresh; Aluko, Rotimi E.; Puniya, Anil Kumar (Frontiers in Food Science and Technology, 2022)
Food-borne diseases are on the rise, and these will likely continue as a public health concern into the coming decades. Majority of foodborne outbreaks are linked to infections by emerging foodborne pathogens such as Campylobacter, Salmonella, Listeria monocytogenes, and Escherichia coli O157:H7. Foodborne pathogen identification becomes crucial in such scenarios to control these pathogens, associated outbreaks, and diseases. Pathogen detection systems have evolved as essential food safety tools to combat microbial threats and experts are striving to develop robust, accurate and ergonomic rapid pathogen-detection kits. Lectin, a ubiquitous biomolecule (sugar binding proteins) present in almost all domains of life is a promising alternative to molecular based methods as a bio-recognition molecule in detection of foodborne pathogens for biosensor applications, owing to its multivalency and spatial organization of ligands. Due to their extensive prevalence, lectin-based biosensors have become the most sought-after bio-recognition molecules in biosensor applications because of increased sensitivity and reduced cost when compared to immune-based biosensors. The current paper discusses the claimed benefits of lectin as a superior bio-recognition molecule, as well as its numerous applications in biosensor creation.